Implementation of The Audio-Lingual Method to Improve Arabic Language Learning Outcomes Among Students at MI Miftahul Khaer Tangerang - Muin, M. Tamsil (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to explore the implementation of the Audio-Lingual Method in enhancing Arabic learning outcomes among fifth-grade students at MI Miftahul Khaer Tangerang, and to analyze its impact on affective, cognitive, and psychomotor domains. Employing a qualitative approach with a case study design, data were collected through participant observation, semi-structured interviews, and instructional documentation. The findings reveal that the teacher consistently applied the Audio-Lingual Method through rehearsed dialogues, sentence pattern drills, and structured verbal role-playing, which stimulated students' active participation in the learning process. Students demonstrated improvements in understanding and producing simple spoken sentences, increased confidence in speaking during class, and better coordination in verbal interactions. Positive responses were also observed in terms of heightened motivation and willingness to use Arabic in daily communication. This study contributes practically to the advancement of Arabic instruction at the elementary level and theoretically reinforces the validity of behaviorist and structural-linguistic theories within local educational contexts. The findings imply a broader applicability of the Audio-Lingual Method in madrasah settings and highlight the need for targeted teacher training in designing oral, repetitive, and contextually grounded language instruction strategies.